Youngs and generational replacement of crafts in the Chamaca district, Cusco - Agreda Paz, Bruno Jesus (2022)
When investigating the situation of handicrafts in the district of Chamaca, province of Chumbivilcas, region of Cusco, it is possible to observe the low participation of young people, in other words, generational change is not guaranteed. Additionally, the dynamics of the globalized market has massified products and diversified cultur-al supply and demand, including handicrafts, reducing its profitability compared to primary activities such as agriculture, which concentrates a large part of the district’s labor demand. The work investigates the relationships that the young people of this district develop with crafts.